MERAJUT KESELARASAN HIDUP MELALUI SENI PERTUNJUKAN: Memori Kolektif Kesenian Rodatin Margo Rukun - Nur Arohman; Sunardi Sunardi; Emy Wuryani (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
The concept of harmony in Javanese society contains ethical principles that must be upheld by the Javanese people. All measures are taken to maintain harmony. Rodatin is a folk performing art that reflects this concept. Rodat dance serves as a medium of Islamic symbols since the reign of Sri Sultan Hamengku Buwono I. Rodatin is a war technique of the Diponegaro War which is camouflaged in the form of smooth movements. Knowledge of this art is limited to oral speech. This paper writes about the collective memory of Rodatin in the Margo Rukun art group in Mulungan Hamlet, Nogosren Village, Getasan District, Semarang Regency, Central Java. From this activity, it can be seen that Rodatin art has a blend of Javanese, Hindu, Islamic and Western values. Rodatin art is performed in the methukan (encounter) tradition in the Javanese-Islamic calendar, namely Rejeb, Ruwah, Pasa, Suro, and Sapar. Methukan is a symbol of hablum minnanas and hablum minnallah (human relations with fellow creatures and humans with the creator). Rodatin art as a means of da'wah and practice to knit the way of harmony in accordance with Javanese and Islamic values.